MULTICULTURALISM IN EUROPEAN EDUCATION POLICY - Krystopchuk, Tatiana (Continuing Professional Education: Theory and Practice, 2019)
The article outlines the basic directions of implementing the principles of multiculturalism in education in European countries. It is stressed an ambivalent solving of the problem of multiculturalism in educational sphere in the EU. The areas of implementing institutional language policy which regulates use of languages within or between EU institutions (creation of lifelong learning programs, training of translators, training of teachers of foreign languages in two or more language specialties, increasing the number of foreign languages taught in the school) are highlighted. It is emphasized that foreign language is regarded as one of the fundamental competencies of knowledge society citizen. The prevalence of English in higher education reform discourse of European countries (globalization, the internationalization of higher education, unification of documents on education, mandatory study of two foreign languages, the priority of English comprehensive programs and projects of international inter-university cooperation, increase of academic mobility of students and teachers) is grounded.